Exploring Human-Generative AI Interaction in L2 Learners’ Source Use Practices: Issues, Trials, and Critical Reflections - Sun, Qingyang (Journal of Academic Writing, 2024)
The emergence of generative Artificial Intelligence (GenAI) tools such as ChatGPT has attracted wide attention in the field of L2 writing and academic writing, but few papers to date have analysed GenAI’s potential application (positive and negative) in source use practices in academic writing. This article discusses three key aspects of source use – academic attribution, searching and reading sources, and source integration. AI tools are trialled for each aspect, followed by an overall SWOT analysis. While writers can use AI tools to assist on several source use practices, they are not recommended to use AI without a deep understanding of academic writing and source use principles. This article concludes with suggestions for student writers, academic support providers, and institutions.